Peningkatan Kreatifitas Peserta Didik Melalui Metode Penugasan - yanti, meini (Jurnal Daya Saing, 2017)
Abstract: The creativity of learners in the learning process is mainly related to the management of education and training is needed and become the standard of competence that should be obtained. But at educational institutions most of the efforts to improve creativity is still not successful. During this effort to foster creativity of learners is based on efforts to motivate and consequently less than optimal. Through the method of assignment with the application of classroom action research and qualitative data analysis obtained the result that through the method of assignment to learners with the limits of assessment results then the creativity of learners in learning is increasing. Keywords: Creativity, Assignment